(untitled) (International Journal of Economics Management and Social Science, 2026)
Managerial decision-making stands at the intersection of rationality, intuition, and cognitive limitation—a tension that Herbert Simon’s bounded rationality model illuminates with enduring relevance. This systematic review and empirical study examine how Indonesian organizational managers navigate complex decisions in conditions of uncertainty, time pressure, and informational constraints. Drawing on a systematic review of 87 peer-reviewed studies published between 2010 and 2024, complemented by a cross-sectional survey of 245 senior managers from public and private organizations in Java, Indonesia, this study assesses the prevalence, predictors, and outcomes of rational, intuitive, and bounded rationality decision-making approaches. Survey findings reveal that pure rational decision-making is rarely employed in practice (18.4%), while intuition-dominant approaches are used by 31.8% of managers and bounded rationality satisficing strategies by 49.8%. Managerial experience, organizational culture, decision complexity, and time pressure significantly predict decision style preferences. Structural equation modeling demonstrates that decision quality—measured by self-reported decision outcomes—is highest when intuition and analytical reasoning are integrated within a bounded rationality framework. The study extends Simon’s model to the Indonesian sociocultural context, identifying the role of social harmony norms (kerukunan), hierarchical organizational cultures, and relational trust in shaping decision-making processes. Keywords: managerial decision-making; bounded rationality; Herbert Simon; intuition; organizational behavior; sociology of organizations; Indonesia